Measuring depth-dependent residual stresses in gaseous nitrided steels using indentation method - Yayla, Ahmet Fatih; Gecu, Ridvan; Solak, Nuri; Kazmanli, Kursat; Urgen, Mustafa (IOP Publishing Ltd, 2024)
This study investigated residual stress evaluations during gaseous nitriding of 50CrMo4 and 31CrMoV9 steels. The nitriding processes were carried out in the NH3/H2/N2 atmosphere at 525 degrees C for 2 h by controlling the nitriding potential. The development of depth-dependent residual stresses was conducted using a Vickers indentation instrument with an estimated geometric correction. The obtained results correlated with the sublayer removal-assisted XRD sin2 psi method. Diffusion layers between 135 and 200 mu m were obtained for all samples upon nitriding. The surface hardness values reached 475 HV for 50CrMo4 and 825 HV for 31CrMoV9 steels. The geometric correction factor alpha was calculated as 78 degrees for a Vickers indenter to measure residual stresses. The generated compressive residual stresses by nitriding increased with increasing nitriding potential by 71% (from -350 to -600 MPa) and 13% (from -750 to -850 MPa) for 50CrMo4 and 31CrMoV9 steels, respectively. An approximately linear relationship was obtained between the hardness and residual stress profiles of the nitrided samples.
Keywords: gaseous nitriding; 50CrMo4 steel; 31CrMoV9 steel; indentation; residual stress; NANOINDENTATION; Materials Science